Arteterapia en el desarrollo de la inteligencia emocional en estudiantes de bachillerato de la Unidad Educativa José Miguel Leoro Vásquez. - Cóndor, Luisa del R. (2022)
The purpose of this research is to propose an alternative use of art therapy that allows the high school student to develop emotional intelligence for a good performance in the educational process. In addition, present as a pedagogical alternative the ART-EMO (Emotions and Art) program that allows the student to develop skills through the use of artistic techniques. In the methodological aspect, the descriptive quantitative approach was used, using simple statistical analysis to analyze the data collected in the field. The analysis and interpretation of results was collected through the BarOn ICE Emotional Intelligence Inventory survey: NA – Complete. The data obtained make it easier to understand the degree of emotional intelligence in high school students in times of pandemic.